Increase in Economic Efficiency of Irrigated Lands in Kazakhstan - BEKBENBETOVA, Bazarkul; TUREBEKOVA, Bazhan; RAKHMETULINA, Zhibek; SEMBIEVA, Lyazat (Journal of Advanced Research in Law and Economics, 2017)
In the article the theoretical bases of formation and introduction into circulation of intercropping discusses. Productivity of land is operably linked to water consumption. An intercropping is one of the possible ways of rational use of water resources and improving productivity of irrigated agriculture.